Mekanisme Penyelesaian Sengketa Klaim Asuransi Tidak Cair Melalui Lembaga Alternatif Penyelesaian Sengketa Sektor Jasa Keuangan (LAPS SJK) (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Disputes over unpaid insurance claims are a problem that frequently arises in insurance practice and can harm consumers both financially and psychologically, while also reducing public trust in the insurance industry. Such disputes are generally triggered by differing interpretations of policy provisions, alleged breaches of the good-faith principle, and administrative obstacles, which ultimately lead to civil conflicts between the insured and the insurer. To provide access to dispute resolution that is faster, fairer, and more affordable than litigation, the Financial Services Authority (Otoritas Jasa Keuangan/OJK) established the Alternative Dispute Resolution Institution for the Financial Services Sector (Lembaga Alternatif Penyelesaian Sengketa Sektor Jasa Keuangan/LAPS SJK) through OJK Regulation No. 61/POJK.07/2020. This study aims to analyze the mechanism for resolving disputes over unpaid insurance claims through LAPS SJK and to assess its effectiveness in providing legal protection and legal certainty for consumers. The research method employed is normative legal research using a statutory approach and a conceptual approach, through an examination of primary, secondary, and tertiary legal materials related to contracts, insurance, consumer protection, and alternative dispute resolution. The findings show that LAPS SJK has the authority to handle civil disputes in the financial services sector, including insurance disputes, provided that the parties have a written agreement and have first pursued internal dispute resolution (Internal Dispute Resolution/IDR). Dispute resolution at LAPS SJK is conducted through mediation and arbitration. Mediation is facilitated by a mediator to encourage the parties to reach a settlement agreement, which may be reinforced into a Deed of Settlement (Akta Perdamaian) that is final, binding, and enforceable. If mediation fails, arbitration offers a more determinative resolution through a final and binding award that can be enforced after being registered with the District Court. Overall, LAPS SJK is considered effective because its procedures are structured, time-bound, and provide a fee waiver for mediation in retail and small-claim cases up to IDR 750,000,000. However, its effectiveness remains conditional, as it depends on the existence of a written agreement between the parties, the obligation to undergo IDR, and good faith in the mediation process.